2017
DOI: 10.1063/1.5001951
|View full text |Cite
|
Sign up to set email alerts
|

On a mechanism of high-temperature superconductivity: Spin-electron acoustic wave as a mechanism for the Cooper pair formation

Abstract: We have found the mechanism of the electron Cooper pair formation via the electron interaction by means of the spin-electron acoustic waves. This mechanism takes place in metals with rather high spin polarization, like ferromagnetic, ferrimagnetic and antiferromagnetic materials. The spinelectron acoustic wave mechanism leads to transition temperatures 100 times higher than the transition temperature allowed by the electron-phonon interaction. Therefore, spin-electron acoustic waves give the explanation for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…[43,59] The existence of spin-polarized plasma in the semiconductor has been predicted by D'yakonov and Perel, [60] which was later verified experimentally in Ref. Thus, we thus conclude that the SSE-QHD model is especially suitable for the study of wave and instability phenomena in the solid-state plasma.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…[43,59] The existence of spin-polarized plasma in the semiconductor has been predicted by D'yakonov and Perel, [60] which was later verified experimentally in Ref. Thus, we thus conclude that the SSE-QHD model is especially suitable for the study of wave and instability phenomena in the solid-state plasma.…”
Section: Discussionsupporting
confidence: 70%
“…In the study of oblique propagation of longitudinal waves, in the electron-ion and electron-positron-ion plasmas, instead of well-known waves like the Langmuir wave and the Trivelpiece-Gould wave, new solutions were found to exist as a result of considering electrons as two different species having spin-up and spin-down. [43] Recently, another application of the SSE-QHD model was presented in Ref. Furthermore, the non-linear evolution of a obliquely propagating SEAW was demonstrated through the Korteweg-de Vries (KdV) equation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12]. It was shown that the electron-spelnon interaction leads to the Cooper pair formation ensuring a mechanism for the high-temperature superconductivity [13]. Experimental analysis of surface spin waves and spin waves in thin films is a subject of current research (see for instance [14]) leading to a possibility of the experimental analysis of the SEAWs.…”
mentioning
confidence: 99%
“…Subsequently, in the Ref. [50] it has been demonstrated that the existence of SEAW leads to an explanation of the mechanism of the electron Cooper pair formation in the high temperature superconductors as result of electron-spelnon interaction (spelnon is the quanta of the SEAW). Moreover, SSE-QHD model applied to study the oblique propagation of longitudinal waves in magnetized spin-1/2 plasmas and found that instead of two well known waves (Langmuir wave and Trivelpiece-Gould wave) four wave solutions appeared in separate spin-up and spin-down degenerate magnetized plasma [43].…”
Section: Analytical Modelmentioning
confidence: 99%